User Experience Evaluation of the Internal Quality Assurance System Application of UIN Malang Using the User Experience Questionnaire - Illahi, Nabil Rahmad; Supriyono (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
User experience can be a measure of acceptance of an application. The user experience measurement aims to provide input in evaluating the development, improvement and maintenance of the UIN Maulana Malik Ibrahim Malang Internal Quality Assurance System (SPMI) application based on the level of user experience using the User Experience Questionnaire (UEQ). 6 aspects of UEQ were chosen because they have advantages over the others. User trust can decrease, even lead to frustration when a user experiences a failure in the user experience. It is feared that the data entered into the SPMI application is inaccurate or seems perfunctory. This has the potential to affect the evaluation and improvement of each study program. This research was conducted to SPMI admins from each study program at UIN Maulana Malik Ibrahim Malang. The results of measuring user experience from the SPMI application of UIN Maulana Malik Ibrahim Malang showed positive evaluation results with categories above the average, namely in the aspects of perspicuity (1.712), dependability (1.470), and stimulation (1.167), novelty (0.917). Meanwhile, in terms of attractiveness (1.626) and efficiency (1.864). The results are included in the good category, but efforts still need to be made to improve the quality of the novelty to be more innovative in its development.